STRATEGI ADAPTASI PETANI DALAM MENGAPLIKASIKAN MEKANISASI PERTANIAN PADA LAHAN BASAH DI KABUPATEN OGAN ILIR SUMATERA SELATAN - Riswani; Thirtawati; Yunita (Politeknik Negeri Lampung., 2023)
Increasing food production, which is currently difficult to do on productive land with an extensification pattern due to limited land availability, causes the exploitation of wetlands with the category of lebak land (marginal land) to be an option for expanding food crops to increase food production in South Sumatra which has a lot of wetlands. Technological engineering is an option in overcoming the constraints of processing lebak land, especially in the use of agricultural tools and machinery which are still low in interest and adoption rates among farmers. This study aims to; (1) formulate strategies so that farmers are interested in cultivating lebak land into productive land, (2) formulate farmer adaptation strategies in cultivating lebak land by applying relevant technology. The survey method was used in this study with two layers of samples (farmers who used Alsintan and farmers who worked on the land manually), as many as 50 respondents in each layer (a total of 100 respondents) were taken using a simple disproportionate random method. Primary and secondary data obtained, processed to calculate income, tested for differences using paired sample t tests, the results of which became the basis for strategies to increase farmers' interest. Formulation of adaptation strategies using the SWOT method with the results of the study: (1) farmers who apply mechanization technology in cultivating rice in lebak land can do their farming with IP 200, incur lower production costs, and higher production and income than farmers who cultivate it manually; (2) The use of mechanization technology is still not efficient in the use of seeds, fertilizers, pesticides, so it must be optimized, (3) The adaptation strategy that must be carried out by farmers is an aggressive strategy because it is in quadrant I, which shows that rice farming in lebak land is in a strong position and has great opportunities to do. This strategy is the main strategy because the strength factors (S) and opportunities (O) owned by farmers in cultivating rice on lebak land have a value greater than the weakness factors (W) and threats (T) that will be encountered.